2014
DOI: 10.1001/jamaophthalmol.2014.397
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Antifungal Additives in Optisol-GS Corneal Storage Medium

Abstract: IMPORTANCE Optisol-GS, the most common corneal storage medium in the United States, contains antibacterial but no antifungal supplementation. Most postkeratoplasty endophthalmitis and keratitis cases are now of a fungal origin.OBJECTIVE To assess the efficacy and safety of voriconazole and amphotericin B in reducing Candida species contamination of Optisol-GS under normal storage conditions. DESIGN, SETTING, AND PARTICIPANTSIn vitro laboratory study using 15 pairs of research-grade donor corneas and 20-mL vial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 26 publications
2
52
1
1
Order By: Relevance
“…Ritterband et al 26 found that adding 100 mg/mL voriconazole to cornea storage medium significantly reduced fungal growth. In contrast, Layer et al, 27 were able to culture C. albicans and C. glabrata from media inoculated with a lower dose of voricazonole (50 mg/mL). However, in samples supplemented with amphotericin B, there was no growth of fungal organisms except at 0.25· and 0.5· minimum inhibitory concentrations.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Ritterband et al 26 found that adding 100 mg/mL voriconazole to cornea storage medium significantly reduced fungal growth. In contrast, Layer et al, 27 were able to culture C. albicans and C. glabrata from media inoculated with a lower dose of voricazonole (50 mg/mL). However, in samples supplemented with amphotericin B, there was no growth of fungal organisms except at 0.25· and 0.5· minimum inhibitory concentrations.…”
Section: Discussionmentioning
confidence: 93%
“…However, in samples supplemented with amphotericin B, there was no growth of fungal organisms except at 0.25· and 0.5· minimum inhibitory concentrations. 27 Although corneas destined for PK are also stored in Optisol-GS, there are several distinct opportunities for fungal growth and contamination associated with precut tissue processing for DSAEK when compared with PK. After harvesting, precut tissue is placed in Optisol and stored at 4°C.…”
Section: Discussionmentioning
confidence: 99%
“…[11-12] Both agents were effective in reducing the incidence of positive cultures. The EBAA has held the position that the low incidence of fungal infections does not warrant the routine use of antifungal medications in storage media.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 In the meantime, a heightened awareness of this condition, along with aggressive treatment should point the practitioner to consider the diagnosis of AK. 9,10 Even when the suspicion is high, confirmation can be difficult as cultures are sometimes unrewarding in terms of a high false negative rate.…”
Section: Q: the Incidence Of Fungal Keratitis Aftermentioning
confidence: 99%